Il lessico dei vasi e dei contenitori greci nei papiri: Specimina per un repertorio lessicale degli angionimi greci - Bonati, Isabella (Archiv für Papyrusforschung und verwandte Gebiete - Beihefte, 2016)
The ancient typology of Greek vases has long posed a difficult problem for scholars of Antiquity. This study adds much-needed clarity by analyzing a representative sample of terms denoting different types of containers in the papyri, a valuable source of linguistic information. It presents a broad overview of each important lemma, critically examining and comparing them with both textual data and archaeological artifacts. Isabella Bonati, University of Parma, Italy.